2019
DOI: 10.1029/2019jb018085
|View full text |Cite
|
Sign up to set email alerts
|

Open Apatite Sr Isotopic System in Low‐Temperature Hydrous Regimes

Abstract: Single crystal in situ Sr and Nd isotopic analysis of apatite permits more accurate interrogation of a variety of geoscience questions, including provenance, petrogenesis, and ore system evolution. However, the degree to which the apatite Sr and Nd isotopic systems remain closed under extended low-temperature hydrous conditions is not well constrained. Granitoids at the Baogutu deposit in NW China contain veins of low-temperature H 2 O-rich epistilbite and thus provide an excellent opportunity to evaluate isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Studies of fluid-mineral interaction in experiments and on natural mineralized rocks have shown that the apatite structure, chemistry and O-Sr-Nd isotopic composition can be modified by moderate to high temperature (300° to 900°C) hydrothermal fluids including H2O-CO2, acidic and alkalic fluids (Harlov and Fӧrster, 2003;Harlov et al, 2005;Migdisov and Williams-Jones, 2014;Li and Zhou, 2015;Zhao et al, 2015;Betkowski et al, 2016;Bouzari et al, 2016;Migdisov et al, 2016;Zeng et al, 2016;Anenburg et al, 2018;Li et al, 2018;Palma et al, 2019). Our previous studies at the Baogutu porphyry Cu deposit (China) have shown that low temperature (<300°C) fluids can modify the apatite structure, chemistry and Sr isotopic composition (Cao et al, 2019b). The altered rocks at Black Mountain are characterised by modifcation of plagioclase by epidote and of biotite by epidote and chlorite, as well as the widespread occurrence of calcite (Fig.…”
Section: The Cause Of Variations In Apatite Chemistrymentioning
confidence: 98%
See 3 more Smart Citations
“…Studies of fluid-mineral interaction in experiments and on natural mineralized rocks have shown that the apatite structure, chemistry and O-Sr-Nd isotopic composition can be modified by moderate to high temperature (300° to 900°C) hydrothermal fluids including H2O-CO2, acidic and alkalic fluids (Harlov and Fӧrster, 2003;Harlov et al, 2005;Migdisov and Williams-Jones, 2014;Li and Zhou, 2015;Zhao et al, 2015;Betkowski et al, 2016;Bouzari et al, 2016;Migdisov et al, 2016;Zeng et al, 2016;Anenburg et al, 2018;Li et al, 2018;Palma et al, 2019). Our previous studies at the Baogutu porphyry Cu deposit (China) have shown that low temperature (<300°C) fluids can modify the apatite structure, chemistry and Sr isotopic composition (Cao et al, 2019b). The altered rocks at Black Mountain are characterised by modifcation of plagioclase by epidote and of biotite by epidote and chlorite, as well as the widespread occurrence of calcite (Fig.…”
Section: The Cause Of Variations In Apatite Chemistrymentioning
confidence: 98%
“…Three different models can explain the origin of distinct apatite characteristics in fresh and altered rocks: (1) inheritance from primary magmas (e.g., Belousova et al, 2002;Chu et al, 2009;Mao et al, 2016); (2) elemental diffusion (Ague and Baxter, 2007); and (3) fluid modification (Harlov and Fӧrster, 2003;Harlov et al, 2005;Migdisov and Williams-Jones, 2014;Li and Zhou, 2015;Zhao et al, 2015;Betkowski et al, 2016;Bouzari et al, 2016;Migdisov et al, 2016;Zeng et al, 2016;Anenburg et al, 2018;Li et al, 2018;Cao et al, 2019b;Palma et al, 2019).…”
Section: The Cause Of Variations In Apatite Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies on granite petrogenesis have benefited from advances in analytical techniques that enable in-situ analysis of minerals for stable and radiogenic isotopes, including O, S, Rb-Sr, Sm-Nd and Lu-Hf systems (e.g., Griffin et al 2002;Yang et al 2014;Economos et al 2017;Bruand et al 2019;Cao et al 2019). Such studies have shown that in-situ geochemical analysis on minerals (e.g., apatite, plagioclase, zircon and titanite) has many advantages over whole-rock chemistry in petrogenetic discussion (e.g., Yu et al 2018;Gros et al 2020;Zhang et al 2020).…”
Section: Petrogenetic Implicationsmentioning
confidence: 99%